Age effect on kinematic variables of stepping after multidirectional disturbances - Silva, Nuno (2015)
Systems with influence on postural control suffer structural and functional changes with aging. Therefore stepping strategies against external disturbances, may have different characteristics between individuals of different age groups. Objectives: To analyze step length, step average speed and step latency on forward-backward disturbances, as well as stepping strategies after lateral disturbances. The relationship between lower limb dominance and response limb was also analyzed.